Contribution of magnetic aftereffect and induction transition characteristics of basalts from the Vitim plateau - Kazanskiy, A. Yu.; Matasova, G. G.; Kozhevnikov, N. O.; Antonov, E. Yu.; Maksimov, P. S. (Geofizicheskiy Zhurnal, 2012)
To study magnetic aftereffect (magnetic viscosity) with its manifestations making difficulties for interpretation of the data of transitional processes, comprehensive experimental studies of samples have been conducted, which characterize the upper rock mass of the Vitim basaltic plateau. An attempt to reveal the character of distribution of magnetically viscous rocks within volcano-sedimentary succession of strata has been made and to find out which ferromagnetic particles display the effect of magnetic viscosity on the inductive transient response. It has been shown that in time-domain measurements with inductive systems the greatest contribution of magnetic viscosity effect is brought by the most fresh, unchanged rocks. Magnetic viscosity effect is mainly caused by super-paramagnetic grains of low-titanic titanomagnetite, close to pure magnetite with rather narrow grain-size interval (most probably 0.0254-0.029 mm). As for the smaller superparamagnetic grains, the contribution of relaxation of their magnetization to inductive transient responses is approximately 3 times lower. Possible criteria of diagnostics of superparamagnetic particles of different size are proposed on the base of petro-magnetic data.